2021
DOI: 10.1177/2167702620954216
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Inflated Prediction Performance: A Commentary on Machine Learning and Suicide Research

Abstract: The use of machine learning is increasing in clinical psychology, yet it is unclear whether these approaches enhance the prediction of clinical outcomes. Several studies show that machine-learning algorithms outperform traditional linear models. However, many studies that have found such an advantage use the same algorithm, random forests with the optimism-corrected bootstrap, for internal validation. Through both a simulation and empirical example, we demonstrate that the pairing of nonlinear, flexible machin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 24 publications
4
47
0
Order By: Relevance
“…Note that while machine learning approaches are valuable and may increase predictive validity, traditional hypothesis testing is also needed to provide an explanation of associations among mHealth variables of interest and mental health. This may be particularly important as recent research indicates that machine learning approaches often inflate predictive performance in mental health research (Jacobucci et al, 2021), although this is not found in all studies (Jacobson et al, 2021). The present study used a novel multimethod approach with wearable indices of biobehavioral functioning as cross-sectional and prospective predictors of adolescent internalizing symptoms across early adolescence.…”
Section: Introductionmentioning
confidence: 96%
“…Note that while machine learning approaches are valuable and may increase predictive validity, traditional hypothesis testing is also needed to provide an explanation of associations among mHealth variables of interest and mental health. This may be particularly important as recent research indicates that machine learning approaches often inflate predictive performance in mental health research (Jacobucci et al, 2021), although this is not found in all studies (Jacobson et al, 2021). The present study used a novel multimethod approach with wearable indices of biobehavioral functioning as cross-sectional and prospective predictors of adolescent internalizing symptoms across early adolescence.…”
Section: Introductionmentioning
confidence: 96%
“…We also report that these models can use different features to achieve similar performance. Different models emphasize different features not simply because of its relevance to a disorder, but because of the mathematics associated with the model 34,35 . The variability of the ranking of features used by our individual models also illustrates the potential danger of using the single highest performing model, which is commonly seen in published literature.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, prominent critiques warn from overreliance on ML methods in suicide research (Siddaway et al, 2020). A recent critical commentary, for example, published in this journal (Jacobucci et al, 2021), challenged the prediction superiority of ML methods over more traditional methods, such as standard logistic regression, and mention a few examples in which both methods achieved similar results (e.g., van Mens et al, 2020). Moreover, the authors have evidenced artificially inflated prediction performances in some machine learning methods (specifically when researchers paired optimism-corrected bootstrap with random forests, instead of using internal validation methods, such as k-fold cross-validation).…”
Section: Challenges and Practical Recommendationsmentioning
confidence: 99%